Reduction of Contractual Penalty in Conformity with Polish Law Against the background of Supranational Legal Regulations - Widerski, Paweł (Review of European and Comparative Law, 2023)
The article discusses the issue of the reduction of contractual penalty according to Polish law against the background of supranational legal regulations. The aim hereof is to determine whether the current regulation of contractual penalty reduction resulting from the provisions of Polish law (Article 484 § 2 of the Civil Code) is consistent with the standards that can be derived from supranational legal regulations, i.e. Resolution (78) 3 Relating to Penal Clauses in Civil Law, the UNIDROIT Principles of International Commercial Contracts, the Principles of European Contract Law, the Draft Common Frame of Reference and the TransLex-Principles, as well as to formulate de lege ferenda conclusions. The article uses the logical-linguistic and legal-comparative method. At first, the legal regulation of contractual penalty reduction in Polish law is presented. Next, the reduction of contractual penalty in the aforementioned supranational soft law regulations is discussed. Lastly, the conclusions of the analysis performed are formulated. Despite some weaknesses, the regulation of contractual penalty reduction in Polish law seems be in line with the solutions contained in the supranational regulations in question. Some changes are required in the catalog of the prerequisites for the reduction of the contractual penalty and limitation of arbitrariness as to the extent thereof.